Resource utilization and productivity loss in persons with spina bifida − an observational study of patients in a tertiary urology clinic in Germany. (7th August 2014) - van Nooten, F. E.; Winnette, R.; Stein, R.; Kissner, M.; Schröder, A.; Jöckel, M.; Raluy‐Callado, M.; Lambrelli, D.; Meinhardt, M.; Wasiak, R.
<x xml:space="preserve">Abstract</x> Background and purpose To investigate resource use and burden associated with spina bifida (SB) in Germany. Methods A questionnaire was used to obtain information on SB‐related healthcare resource use and assistive technologies used for the last 1 and 10 years. Individuals with SB were recruited at a tertiary specialist clinic. To participate, persons with SB required the cognitive ability to respond or a caregiver to answer questions on their behalf. They could use personal medical charts or other records to answer. The analyses included assessment of frequency and extent of resource use for both time frames. Results Data on 88 persons with a diagnosis of SB were collected (44% female). During the last year, 88.6% (N = 78) reported at least one visit to a general practitioner's (GP's) office, 77.3% (N = 68) to a urologist and 69.3% (N = 61) to a physiotherapist. The annual average number of visits was 7.6 GP, 3.6 urologist and 65.3 physiotherapist visits. Amongst those hospitalized, a single hospitalization lasted 7.3 days on average, whereas the average annual number of hospital days was 14.8 days. During the previous 10 years, 67.0% (N = 59) of responders used a wheelchair, 64.7% (N = 57) used glasses and 59.1% (N = 52) used orthopaedic shoes, with an average of 2.5, 2.8 and 6.1 new items used, respectively. Conclusions The results indicate that persons with SB require a substantial amount of interaction with healthcare providers, as well as other healthcare‐related resource use, both in the shorter and longer terms.